Meta-Analysis of the Effectiveness of Using Antiplatelet Drugs Uptake in Decreasing Mortality in COVID-19 Patients - Nurhayati, Happy; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Viscoelastic coagulation testing in COVID-19 patients often found elevated concentrations of D-dimer and fibrinogen. Thrombotic complications can be in the form of Venous Thromboembolism (VTE), where this thrombotic disease is one of the factors associated with increased mortality of COVID-19 patients. This study aims to analyze the effectiveness of antiplatelet drugs in reducing mortality in COVID-19 patients.Subjects and Method: This is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2020-2021 using PubMed, Science Direct, Google Scholar, and Scopus databases. The article search was carried out by considering the eligibility criteria defined in the PICO model. Population= COVID-19 patients, Intervention= using antiplatelet drugs, Comparison= not using anticoagulant drugs, Outcome= mortality. The keywords used were